THE IDEA OF ORIGINATION OF INSTITUTION OF A STATE IN THE BUDDHIST PERSPECTIVE (Bodhi Path, 2020)
The religion of Lord Buddha is concerned with the human, its life and behavior. Therefore the Buddha’s education is primarily concerned with human welfare and emancipation.1 The doctrines of Buddhism are well known as the doctrines of human beings, by human beings, and for human beings. It is therefore the doctrines of Buddhism that have performed a unique function in shaping the theoretical, social and religious modes of life. Thus it is not interpreted only on religious perspective but also among others which include economic, social-political perspectives too. In Indian history, the sixthcentury was marked as the centaury of changes in the socio-religious arena. These variations also touch the politicalcharacteristic. At that time the institution of state was termed as an absolute necessity for an orderly society is which is also reflected in the early literature such as Arthasâstra, Dharmasâstra and the Nitisâstra which reflects the system ofancient Vedic political thought and institutions. Buddhism and Jainism which were the dominant philosophies during the time of the sixth century, their written records have also mentioned the background and reasons of origin of the institution of the state, its government, and the concept of kingship and their functions and administrative structure in detailed. The philosophies of Jainism and Buddhism in their written records focused on the necessity and urgency ofthe political system which included the social order, position of the ruler and its functions towards the society.
Keywords: ORIGINATION OF INSTITUTION; BUDDHIST PERSPECTIVE